Effects of azadirachtin on Rhodnius prolixus: immunity and trypanosoma interaction - Azambuja, Patricia de (1992)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Bioquímica e Biologia Molecular. Rio de Janeiro, RJ, Brasil.